Investigation of Viral Escape Mutations within HCV P7 during Treatment with Amantadine in Patients with Chronic Hepatitis C. Issue 6 (August 2013) - Vermehren, Annika; Welsch, Christoph; Elsler, Ulrike; Vermehren, Johannes; Herrmann, Eva; Sarrazin, Christoph; Von Wagner, Michael; Susser, Simone; Hofmann, Wolf Peter; Kronenberger, Bernd; Zeuzem, Stefan; Mihm, Ulrike
Background: Combination of several direct-acting antiviral agents will be necessary to overcome viral resistance in interferon-free treatment regimens for chronic HCV infection. HCV p7 inhibitors may be part of such combination regimens. Understanding why amantadine, despite showing inhibition of HCV p7 in vitro, appears ineffective in clinical trials, may help in the design of novel HCV p7 inhibitors. So far it is unknown whether viral escape mutations within HCV p7 explain the ineffectiveness of amantadine in vivo . Methods: Pretreatment HCV p7 was directly sequenced in 157 consecutive patients with chronic HCV genotype 1b infection who had been treated with amantadine/placebo plus pegylated interferon (PEG-IFN)-α2a/ribavirin within a multicentre clinical trial. Triple therapy was preceded by 2 weeks of amantadine/placebo monotherapy. In nine patients, clonal sequencing was performed at baseline and after 2 weeks of amantadine/placebo monotherapy. Results: Changes of the relative frequency of amino acid substitutions by ≥20% between pretreatment and week 2 of monotherapy were considered potential resistance mutations if they were only found in patients receiving amantadine but not in patients receiving placebo. Seven substitutions fulfilling these criteria were identified in the subset of patients with clonal sequencing. However, none of these substitutions were associated with treatment outcome in the complete cohort of patients receiving triple therapy with amantadine. Conclusions: Potential viral escape mutations within HCV p7 do not seem to play a major role for treatment response to antiviral therapy with amantadine and PEG-IFN-α2a/ribavirin in patients with chronic HCV genotype 1b infection.